Trajectory Planning and Simulation of 6-SPU Parallel Robot - Wencai Liu; Yong Xu; Jiali Chen; Zheng Liang (Jixie chuandong, 2019)
Aiming at the requirements of high machining accuracy and high production efficiency for large workpieces such as aircraft wings in the field of aviation manufacturing. Firstly, the degree of freedom of 6-SPU parallel robot is analyzed by using screw theory, and the trajectory planning of moving platform of the 6-SPU parallel mechanism is analyzed and studied based on the inverse kinematics method and three element space vector according to the Frenet-Serret, the movement platform corresponding position and gesture in the processing process is got. Then, the homogeneous coordinate transformation matrix and the inverse solution calculation formula are used to further determine the movement rules exerted on the end actuator when it is moving on the desired trajectory. Finally, the virtual model of this mechanism is created in SolidWorks software and the planning trajectory is verified through simulation in Simulink simulation module in MATLAB modeling simulation, and the theoretical foundation for the engineering design of mobile parallel processing platform is provided.